Buckling analysis of simply supported composite laminates subjected to an in-plane compression load by a novel mesh-free method - Bui, Tinh Quoc (Vietnam Journal of Mechanics, 2011)
Buckling analysis of composite laminates under an in-plane compression load based on the mesh-free Galerkin Kriging method is presented. The moving Kriging interpolation (MK) technique possessing the delta property is employed to construct the shape functions, and thus no special techniques for imposing the essential boundary conditions are required. The present formulation is based on the Kirchhoff plate theory. The applicability, the accuracy and the effectiveness of the method are illustrated through a number of numerical examples. The results calculated by the proposed method are compared with those of existing reference solutions available in the literature and very good agreements are observed. It can be said that the proposed method can be considered as an alternative numerical technique in terms of meshfree methods.